Rasio Keuangan Bank Terindikasi Bermasalah Oleh BPK Awal Tahun 2020 - Triyogo Moelyo Adhi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2021)
Abstrak: Pada awal tahun 2020 dunia perbankan indonesia dihebohkan dengan laporan dari Badan Pemeriksa Keuangan yang menginikasikan beberapa bank nasional yang bermasalah. Dalam penelitian ini difokuskan pada bank BTN, bank Banten, bank Bukopin, bank Mayapada dan bank Yudhabakti yang memungkinkan didapatkan datanya guna penelitian. Dari beberapa variabel yakni Capital Adequacy Ratio, Return on Asset, Loan Deposit Ratio serta perimbangan Biaya operasional terhadap pendapatan operasional bank terkait selama periode tahun 2016 hingga 2019 tampak bahwa memang beberapa bank tersebut mengalami permasalahan . permasalahan terkait dengan profitabilitas dialami oleh bank Banten, demikian juga dengan perimbangan biaya operasional terhadap pendapatan operasional bank Banten menunjukan indikasi yang sangat mengkhawatirkan. Tingkat likwiditas yang dialami oleh bank BTN sangat tinggi dimana perbandingan antara jumlah kredit yang diberikan dengan jumlah dana deposan dan modal sendiri sudah mencapai rata rata diatas 100% dalam periode 2016 hingga 2019. Hal ini tentu saja memperlukan perhatian dari management untuk lebih memperhatikan arus kas masuk dari pembayaran bunga kredit dan angsuran pokok pinjaman yang diberikan. Kata kunci : capital adequacy ratio, return on asset, loan to deposits ratio , biaya operasional terhadap pendapatan Abstract: At the beginning of 2020, the indonesian banking world was enraged by a report from the Audit Board that indicated several national banks were troubled. In this research focused on BTN bank, Banten bank, Bukopin bank, Mayapada bank and Yudhabakti bank that allows data to be obtained for research. From several variables, namely Capital Adequacy Ratio, Return on Asset, Loan Deposit Ratio and balance of operational costs to the operational income of related banks during the period of 2016 to 2019, it appears that some of these banks experienced problems. Problems related to profitability experienced by Banten banks, as well as the balance of operational costs to the operational income of Banten banks shows a very worrying indication. The level of likwiditas experienced by BTN banks is very high where the comparison between the amount of credit given and the amount of depositors' funds and their own capital has reached an average of above 100% in the period 2016 to 2019. This of course complicates the attention of the management to pay more attention to the cash inflows from loan interest payments and principal installments of loans provided. A well-prepared abstract enables the reader to identify the basic content of a document quickly and accurately, to determine its relevance to their interests, and thus to decide whether to read the document in its entirety. The Abstract should be informative and completely self-explanatory, provide a clear statement of the problem, the proposed approach or solution, and point out major findings and conclusions. The Abstract should be 100 to 250 words in length. The abstract should be written in the past tense. Standard nomenclature should be used and abbreviations should be avoided. No literature should be cited. The keyword list provides the opportunity to add keywords, used by the indexing and abstracting services, in addition to those already present in the title. Judicious use of keywords may increase the ease with which interested parties can locate our article. Keywords: capital adequacy ratio, return on assets, loan to deposits ratio, operating expenses to income